Examination of text's lexis using a Polish dictionary - Voitovych, Roman; Łukasik, Edyta (Journal of Computer Sciences Institute, 2021)
This paper presents an approach to compare and classify books written in the Polish language by comparing their lexis fields. Books can be classified by their features, such as literature type, literary genre, style, author, etc. Using a preassembled dictionary and Jaccard index, we managed to prove a compact hypothesis concerning similar books. Further analysis with the PAM clustering algorithm presented a lexical connection between books of the same type or author. Overall static behaviour of similarities of any particular field on one side and some anomalous tendencies in other cases suggest that recognition of other features is possible. The method presented in this article allows drawing conclusions regarding the connection between any arbitrary books based solely on their vocabulary.